Retrospective Evaluation of Lung Adenocarcinoma Patients Progressing on 1st Line Chemotherapy - Heikki Vilhonen; Samu Kurki; Tarja Laitinen; Samuli Hirsjärvi (My University, 2022)
Background and Objectives: Evaluation of data from electronic health care records could help in guiding towards more rational drug treatments. This single center study evaluated clinical characteristics that could be associated with disease progression. Methods: This was a real world data (RWD) study using existing data from the registries of a university hospital. Patients had lung adenocarcinoma and they had received 1st line treatment. Treatment patterns and survival parameters were characterized and clinical characteristics of the patients were evaluated together with their association with disease progression. Results: 80 stage III/IV patients fulfilling inclusion criteria were identified. Mean age was 62 years and 61% were men. In total, 65% were current smokers and 82% had performance status (ECOG) 0/1. Median progression free survival (mPFS) and median overall survival (mOS) for stage III and IV patients were 8.5 and 5.4 months, and 21.9 and 8.6 months, respectively. The study found that 69% of patients progressed within 9 months from the start of the 1st line treatment. Poor performance status (ECOG 3), male gender, and smoking suggested faster disease progression. Most had received cis/carboplatin-based treatment in the 1st line. Cisplatin regimens were associated with more complete responses and better PFS and OS than the carboplatin ones. Conclusions: By combining algorithmic and manual validation of electronic health care records, clinically valid characteristics and outcomes could be evaluated and presented. This approach forms a basis for tools such as quality registries that can guide treatment decisions.